The Effect of Profitability and Leverage on Firm Value in Food & Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the Period 2020–2024 - Sri Mulyani; Emy Setiawati Melati Putri; Dewi Nur Anisah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to examine the effect of Return on Equity (ROE) and Debt to Asset Ratio (DAR) on Firm Value. The population used in this study consists of all food & beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. This research employs a quantitative method. The sampling technique used is purposive sampling based on predetermined criteria. The total population of food and beverage companies is 102, and after applying the sampling criteria, 29 companies were selected over a 5-year period, resulting in 145 research samples. The data used are secondary data in the form of financial statements obtained from www.idx.co.id and the respective company websites. The analytical technique applied is multiple linear regression using IBM SPSS 25 software.The results show that Return on Equity (ROE) has no significant effect on Firm Value. Meanwhile, Debt to Asset Ratio (DAR) has a significant effect on Firm Value. Simultaneously, the results indicate that Return on Equity (ROE) and Debt to Asset Ratio (DAR) have a positive effect on Firm Value.